Capable Guardians in the Digital Environment: The Role of Digital Literacy in Reducing Phishing Victimization. Issue 12 (2nd December 2017) - Graham, Roderick; Triplett, Ruth
ABSTRACT: In this study, we use Routine Activities Theory to explore the role of digital literacy, a measure of guardianship, in the receipt of and response to phishing. Data for the study come from a nationally representative survey conducted by the American Association of Retired Persons. The analysis results in two conclusions. First, respondents with higher levels of digital literacy report receiving phishing e-mails more often, but report responding to them less. Second, the social position of a respondent matters, but largely for the receipt of phishing. These findings indicate that digital literacy significantly effects the receipt of and response to phishing.